The Effectiveness of Training Methodology on Innovative Work Behavior and Government Employee Performance during the Covid-19 Pandemic: The Role of Soft Skill and Emotional Intelligence - Fonda Ambita Sari; Lia Amalia (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to determine the effect of training methodologies on innovative work behavior and employee performance mediated by emotional intelligence and soft skills during the Covid-19 pandemic. Design/Methods/Approach: The object of this research is the employees of the State Civil Apparatus. They work in the field of education, especially in Jakarta. This study uses a quantitative approach with the Partial Least Square (PLS) analysis method to estimate the suitability of the hypothesized model. The total sample size is 160 respondents, obtained using the saturated sampling technique. Validity and reliability tests are conducted with 70 questions using the SmartPLS 3.0 application. Findings: This study finds that training methodology has a significant effect on innovative work behavior and employee performance, training methodology has a significant effect on soft skills and emotional intelligence, and the mediating role of emotional intelligence and soft skills has a positive and significant effect between training methodology on innovative work behavior and employee performance. Originality: This study develop a new frame work and use Covid-19 pandemic period as a background setting